2008
DOI: 10.1089/jir.2008.0125
|View full text |Cite
|
Sign up to set email alerts
|

Production of Cytokines and Stimulation of Resistance to Viral Infection in Human Leukocytes by Scutellaria baicalensis Flavones

Abstract: Extracts of Scutellaria baicalensis display a wide spectrum of antiviral activity. It was of great interest to check the effect of baicalein and wogonin preparations on two important mechanisms of innate immunity: the secretion of cytokines and the natural resistance of human leukocytes to viral infection. To study the effect of S. baicalensis extracts on interferons (IFNs), tumor necrosis factor alpha (TNF-alpha), and interleukin (IL) production and virus replication, uninfected and vesicular stomatitis virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Astragalus polysaccharides and astragalosides showed strong promoting effects on the phagocytosis of Mycobacterium tuberculosis and on the secretion of interleukin (IL)-1 beta, IL-6 and tumor necrosis factor-alpha by activated macrophages from mice (Xu et al 2007). The major constituents of S. baicalensis are flavonoids -baicalein, baicalin, wogonin, wogonoside, and skullcapflavone -which have been associated with various properties in inducing a broad spectrum of antiviral (Błach-Olszewska et al 2008), antiinflammatory (Hsieh et al 2007), and anticancer actions (Li-Weber 2009). The crude drug ingredients of S. baicalensis showed powerful anti-trypanosomal (Yabu et al 1998) and antibacterial activities (Yang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Astragalus polysaccharides and astragalosides showed strong promoting effects on the phagocytosis of Mycobacterium tuberculosis and on the secretion of interleukin (IL)-1 beta, IL-6 and tumor necrosis factor-alpha by activated macrophages from mice (Xu et al 2007). The major constituents of S. baicalensis are flavonoids -baicalein, baicalin, wogonin, wogonoside, and skullcapflavone -which have been associated with various properties in inducing a broad spectrum of antiviral (Błach-Olszewska et al 2008), antiinflammatory (Hsieh et al 2007), and anticancer actions (Li-Weber 2009). The crude drug ingredients of S. baicalensis showed powerful anti-trypanosomal (Yabu et al 1998) and antibacterial activities (Yang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The major constituents of S. baicalensis are flavonoids: baicalein, baicalin, wogonin, wogonoside, and skullcapflavone, which have been associated with various properties such as antioxidant, anti-inflammatory, antithrombotic, antibacterial, antiviral (Broncel 2007;Hsieh et al 2007;Błach-Olszewska et al 2008), and anticancer (Li-Weber 2009). The crude drug ingredients of S. baicalensis showed powerful antitrypanosomal (Yabu et al 1998).…”
Section: Chemistrymentioning
confidence: 99%
“…Previous studies have demonstrated that Sb extracts containing different amounts of baicalein and wogonin modulate cytokine productions such as TNF-alpha and IL (IL-12, IL-10) production in peripheral blood leukocytes and transforming growth factor b1 (TGF-b1) in RAW 264.7 mouse macrophage cell line. 24,25) A large number of studies have shown the anti-inflammatory effect of Sb and its active compounds was through suppression of IL-6, NF-kB or AP-1 signaling pathways in many disease models. [26][27][28] However, under the situation of liver regeneration, cytokines such as tumor necrosis factor-a (TNF-a) and IL-6 are the key factors in priming the hepatocytes and subsequently stimulating the growth of hepatocytes.…”
Section: Disucssionmentioning
confidence: 99%